Enhancing the Anticancer Activity of Squamocin for Breast Cancer Treatment Using Nanodiamond Nanoparticles: An In Vivo Study - Dewi, Firli Rahmah Primula; Sri Puji Astuti Wahyuningsih; Ahmar, Rasyidah Fauzia; Na'ilah Insani Alifiyah; Lim, Vuanghao; Prenggono, Muhammad Darwin (HAYATI Journal of Biosciences, 2022)
Squamocin is one of the annonaceous acetogenins produced by the Annonaceae family and displays potent anti-cancer activity against cancer cell lines. This study aimed to investigate the growth inhibition activity of squamocin coupled with nanodiamond on rats (Rattus norvegicus)-induced breast cancer. Twenty-five female R. norvegicus were divided into five groups (n = 5), including normal control (without any treatment), negative control, group treated with nanodiamond only (ND), group treated with squamocin only (SQ), and the group treated with squamocin coupled with nanodiamond (NDSQ). All of the animal models were induced for breast cancer, except for the normal control group. Breast cancer induction was performed using two doses of N-nitroso-N-methylurea (NMU) injection (50 and 30 mg/kg body weight) intraperitoneally and waited for 22 weeks until the tumor was detected to formed. Nanodiamond coupled with squamocin were administered by intraperitoneal injection (1.5 mg/kg body weight) for 5 weeks, one injection per 3 days. This study showed that the treatment with squamocin coupled with nanodiamond (NDSQ) significantly reduced the proliferation (Ki-67) and induced apoptosis (Caspase-3) of breast cancer cells, corresponding to the reduction of the thickness of the mammary ductal epithelium (p